Oligodendrocyte progenitor cells differentiation of nuclear transferred mouse embryonic stem cells - Salehi, M; Ardeshirylajimi, A; Mossahebi-Mohammadi, M; Kondori, Z; Jorjani, M (Cellular and Molecular Biology, 2015)
Central nervous system (CNS) injuries cause to variable disorders in people around the world without any decisive treatment. Use of embryonic stem cells (ESCs) would be helpful in repairing of neural system damages. Somatic cell nuclear transfer (SCNT) is a way for implanting ESCs with lowest possible rejection. In the present study, mouse nuclear transfers ESCs (ntESCs) ability in differentiation to oligodendrocyte progenitor cells (OPCs) was investigated by morphological study, RT-PCR and flow cytometry analysis. Bi-polar and tri-polar, OPCs were observed in stem cells cultured in differentiation medium after four weeks. Result of gene expression analysis demonstrated that differentiated stem cells were expressed most important OPCs related gene markers after differentiation period. Moreover, flow cytometry analysis carried out to confirm other results that showed differentiated stem cells significantly expressed NG2 and O4 as critical OPC surface markers. Taken together, it seems that mouse ntESCs showed highly potential for OPC differentiation and could be an appropriate candidate for stem cell therapies.